2019
DOI: 10.1093/mnras/stz2111
|View full text |Cite
|
Sign up to set email alerts
|

Narrow, intrinsic C iv absorption in quasars as it relates to outflows, orientation, and radio properties

Abstract: This work provides evidence that a large fraction of C iv narrow absorption lines (NALs) seen along the line of sight to distant quasars are due to accretion disk winds, while also seeking to understand the relationship between NALs and certain quasarintrinsic properties. We extend the results from past work in the literature using ∼ 105, 000 NALs from a sample of ∼ 58, 000 SDSS quasars. The primary results of this work are summarized as follows: (1) the velocity distribution (dN/dβ) of NALs is not a function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 90 publications
2
12
1
Order By: Relevance
“…Our study provides this confirmation in the BOSS dataset that is unbiased for NAL properties. Our study also confirms the most recent work by Stone & Richards (2019), who estimated that ∼30% high-velocity NALs are intrinsic. We need to note that high-velocity NALs are correlated with both BAL outflows and radio-loudness, but BALQ-SOs are generally radio quiet (discussed in Chen et al 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study provides this confirmation in the BOSS dataset that is unbiased for NAL properties. Our study also confirms the most recent work by Stone & Richards (2019), who estimated that ∼30% high-velocity NALs are intrinsic. We need to note that high-velocity NALs are correlated with both BAL outflows and radio-loudness, but BALQ-SOs are generally radio quiet (discussed in Chen et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…We examine NALs at large velocity shifts to determine if a fraction of them form in high-speed quasars instead of cosmologically-intervening gas or galaxies. Correlations with other quasar properties would provide direct evidence for an outflow origin (e.g., Richards et al 1999;Richards 2001;Stone & Richards 2019, and Section 1). Figure 3 shows the fractions of quasars with highvelocity C iv NALs in the high-v40 group for BALQSOs and non-BALQSOs.…”
Section: High-velocity Nalsmentioning
confidence: 99%
“…Thus, whether the gas is associated with the central engine or the host galaxy, AAL0s might be expected to be more common in relatively edge-on orientations. Such an explanation for AAL0s would be consistent with the findings of Stone & Richards (2019) and could provide an orientation indicator for both radio-loud and radioquiet quasars that exhibit AAL0s.…”
Section: The Hypothesissupporting
confidence: 79%
“…As a result of that process, it has become clear that what was once thought to be a distribution of C IV absorption line systems representing "cluster" gas with velocities within ±1000 km s −1 of the systemic redshift (Foltz et al 1986;Anderson et al 1987) are more likely a combination of outflowing material and "virialized" material that is at much lower velocity (Bowler et al 2014). Stone & Richards (2019) argued that systems with "zero-velocity associated absorptionline systems" (hereafter AAL0s), may be an orientation indicator for radio-quiet quasars given that (1) in radioloud quasars these systems are observed preferentially in steep-spectrum radio sources that are presumed to have an edge-on orientation, and (2) that they are just as common in radio-quiet quasars as in radio-loud quasars.…”
Section: The Hypothesismentioning
confidence: 99%
“…Kratzer & Richards (2015), also using FIRST and SDSS, were able to show that the mean radio-loudness decreases with increasing C IV blueshift and argue that radio-loud and radio-quiet quasars should not be compared without first taking into account non-radio properties. Stone & Richards (2019) investigated instead the narrow C IV absorbers associated with the quasar and found them to be as common in radio-quiet quasars as they are in radio-loud quasars, suggesting that whatever physics governs the associated absorbers -whether they are evidence of a failed accretion disc wind (e.g. Vestergaard 2003) or winds from star formation on kiloparsec scales (Barthel et al 2017) -it is unrelated, at least directly, to the radio emission (see also Chen et al 2020, who found no correlation between the number of absorbers in quasar spectra and radio-loudness).…”
Section: Introductionmentioning
confidence: 99%